A review of newer therapy in dengue fever (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Dengue is a viral disease that at present affects an enormous number of people in over 125 countries and is conscientious for a sizable number of deaths. There is no antiviral chemotherapy or vaccine for dengue virus and management of the disease is done on supportive measures, so various treatments are being investigated. Studies have indicated that the juice of the leaves of the Carica papaya plant from the family Caricaceae could help to increase the platelet levels in these patients. This review explains some of the published studies on this topic. Although many of the studies and case reports published in literature lack adequate information, some of the studies do raise the possibility that this treatment could be an important option in the future. Further large scale studies could establish the usefulness or ineffectiveness of this natural product in the treatment of dengue.